A functional screen identifies miRNAs that inhibit DNA repair and sensitize prostate cancer cells to ionizing radiation - Koji Hatano; Binod Kumar; Yonggang Zhang; Jonathan B. Coulter; Mohammad Hedayati; Brian M. Mears; Xiaohua Ni; Tarana A. Kudrolli; Wasim H. Chowdhury; Ronald Rodríguez; Theodore L. DeWeese; Shawn E. Lupold (2015)
MicroRNAs (miRNAs) have been implicated in DNA repair pathways through transcriptional responses to DNA damaging agents or through predicted miRNA regulation of DNA repair genes. We hypothesized that additional DNA damage regulating miRNAs could be identified by screening a library of 810 miRNA mimetics for the ability to alter cellular sensitivity to ionizing radiation (IR). A prostate cancer Metridia luciferase cell model was applied to examine the effects of individual miRNAs on IR sensitivity. A large percentage of miRNA mimetics were found to increase cellular sensitivity to IR, while a smaller percentage were protective. Two of the most potent IR sensitizing miRNAs, miR-890 and miR-744–3p, significantly delayed IR induced DNA damage repair. Both miRNAs inhibited the expression of multiple components of DNA damage response and DNA repair. miR-890 directly targeted MAD2L2, as well as WEE1 and XPC, where miR-744–3p directly targeted RAD23B. Knock-down of individual miR-890 targets by siRNA was not sufficient to ablate miR-890 radiosensitization, signifying that miR-890 functions by regulating multiple DNA repair genes. Intratumoral delivery of miR-890 mimetics prior to IR therapy significantly enhanced IR therapeutic efficacy. These results reveal novel miRNA regulation of DNA repair and identify miR-890 as a potent IR sensitizing agent.